ChemInform Abstract: Palladium‐Catalyzed Regioselective ortho‐Acylation of Azoxybenzenes with Aldehyde Derivatives. Issue 19 (May 2015) - Sun, Meng; Hou, Le‐Kai; Chen, Xiang‐Xiang; Yang, Xiao‐Juan; Sun, Wei; Zang, Yu‐Shi
Abstract: An efficient strategy for the regioselective ortho‐acylation of azoxybenzenes with various aldehydes in the presence of palladium catalysts is developed and furnishes good to excellent yields.